Cytopenia first – hepatitis second: an unusual sequence in aplastic anemia - Alashkar, Ferras (Clin Case Rep, 2017)
To the best of our knowledge, this is the first report of aplastic anemia (AA) preceding autoantibody‐negative autoimmune hepatitis (AIH) with successful treatment of both conditions with the same immunosuppressive regimen, resulting in hematopoietic reconstitution and remission of AIH.